Clinical and immunological characteristics of a pediatric population with food protein‐induced enterocolitis syndrome (FPIES) to fish. Issue 3 (27th January 2016) - González‐Delgado, Purificación; Caparrós, Esther; Moreno, M Victoria; Clemente, Fernando; Flores, Emilio; Velásquez, Laura; Rubio, Gonzalo; Fernández, Javier
Abstract: Background: Food protein‐induced enterocolitis (FPIES) is an uncommon, non‐IgE‐mediated food allergy that usually debuts in infancy with profuse vomiting, lethargy, and pallor 2–4 h following ingestion of the offending food. Its immune mechanism is not known. We aimed to describe the clinical features and outcome of children with fish‐FPIES as well as to investigate on cellular immune response implicated. Methods: Prospective and follow‐up clinical study of children with FPIES by fish over a period between 2004 and 2013 was conducted. Measurement in vitro of both cytokine production in peripheral blood mononuclear cells (PBMCs) and expression of HLA‐DR in monocyte‐derived dendritic cells stimulated with fish extracts. Results: Sixteen children (seven male and nine female) were included, with a mean age of onset at 10 months. Diagnosis was established after a median of 4 reactions. Twelve patients were treated in emergency room, and two were admitted in intensive care. Patch tests were positive in six patients. Skin prick tests (SPTs) and specific IgE to all fish tested were negative. Only three children reached tolerance at a mean age of 4.5 years. Eight children avoided fish because of positive oral food challenge (OFC) after 6 years of age. Other patients have not been challenged because of parent refusal to OFC or a recent diagnosis. TNF‐α was increased in patients, and a significant elevation of the HLA‐DR marker was also observed in these patients vs. control donors. Conclusions: FPIES caused by fish in many cases presents with severe clinical manifestations. Patch test has poor diagnostic value, and OFC is the gold standard to test tolerance. The cytokine TNF‐α may be implicated in the clinical symptoms. Higher expression of HLA‐DR in dendritic cells has also been detected in our patients.